Melting rate correlation with batch properties and melter operating conditions during conversion of nuclear waste melter feeds to glasses. (1st April 2021) - Lee, SeungMin; Cutforth, Derek A.; Mar, Derek; Klouzek, Jaroslav; Ferkl, Pavel; Dixon, Derek R.; Pokorny, Richard; Hall, Mark A.; Eaton, William C.; Hrma, Pavel; Kruger, Albert A.
Abstract: The rate of conversion of nuclear waste melter feed to glass is affected by the selection of melter feed materials and by melter design and operation. The melting rate correlation (MRC) is an equation that relates the glass production rate with two types of variables: (a) feed and melt properties: conversion heat, cold‐cap bottom temperature, and glass melt viscosity; and (b) melter design and operation parameters: melter geometry, melter operating temperature, and gas bubbling rate. The MRC shows good agreement for an extended melting rate data set of high‐level waste (HLW) melter feeds and a data set generated for low‐activity waste (LAW) melter feeds. Laboratory observation of heated melter feed samples is often used to assess the cold‐cap bottom temperature of HLW melter feeds (moderately foaming feeds), but this technique appears inadequate for LAW melter feeds (vigorously foaming feeds). For LAW feeds, an adequate assessment of the cold‐cap bottom temperature was achieved using evolved gas analysis, which allows identification of the collapse of primary foam for oxidized feeds. This assessment shows that the cold‐cap bottom temperature for vigorously foaming LAW feeds is higher than that for moderately foaming HLW feeds. When the results of MRC are compared, LAW feeds are generally less sensitive to the bubbling rate and melt viscosity, and more sensitive to the cold‐cap bottom temperature than HLW feeds. The MRC qualifies as a promising tool to support the selection of melter feed materials and melter operating conditions, which is determined from expensive independent scaled melter experiments, and sophisticated mathematical models.